Fully automatized high‐throughput enzyme library screening using a robotic platform. Issue 7 (3rd February 2016) - Dörr, Mark; Fibinger, Michael P.C.; Last, Daniel; Schmidt, Sandy; Santos‐Aberturas, Javier; Böttcher, Dominique; Hummel, Anke; Vickers, Clare; Voss, Moritz; Bornscheuer, Uwe T.
ABSTRACT: A fully automatized robotic platform has been established to facilitate high‐throughput screening for protein engineering purposes. This platform enables proper monitoring and control of growth conditions in the microtiter plate format to ensure precise enzyme production for the interrogation of enzyme mutant libraries, protein stability tests and multiple assay screenings. The performance of this system has been exemplified for four enzyme classes important for biocatalysis such as Baeyer–Villiger monooxygenase, transaminase, dehalogenase and acylase in the high‐throughput screening of various mutant libraries. This allowed the identification of novel enzyme variants in a sophisticated and highly reliable manner. Furthermore, the detailed optimization protocols should enable other researchers to adapt and improve their methods. Biotechnol. Bioeng. 2016;113: 1421–1432. © 2016 Wiley Periodicals, Inc. Abstract : A fully automatized robotic platform for high‐throughput screening of enzyme mutant libraries has been developed covering all steps required ( E. coli growth, enzyme production, cell lysis, and biochemical assays). Dörr et al. exemplify its functionality for four enzyme classes: amine transaminase, Baeyer–Villiger monooxygenase, haloalkane dehalogenase, and an acylase. This allowed the identification of improved enzyme variants in a very precise fashion.